2006
DOI: 10.1590/s0100-84042006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Mobilização de água e conservação da viabilidade de embriões de sementes recalcitrantes de ingá (Inga vera Willd. subsp. affinis (DC.) T. D. Pennington)

Abstract: -(Water mobilization and viability conservation of embryos of recalcitrant seeds of "ingá" (Inga vera Willd. subsp. affinis (DC.) T. D. Pennington). The water content of anhydrobiotic (orthodox) seeds is usually reduced to low values and its metabolism is reduced to a level that viability can be preserved for long periods. In contrast, typical non-anhydrobiotic (recalcitrant) seeds are intolerant to desiccation, possess lower longevity, and need a minimum water level to maintain viability, but the metabolism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
15

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 10 publications
5
26
0
15
Order By: Relevance
“…This was indeed the case in embryos stored in PEG at 5°C with ABA, at 5°C with ABA and HS and at 20°C without ABA or HS. However, a significant increase in MC was The longest effective storage period for Inga embryos was reported by Andréo et al (2006) working with nondried embryos stored in PEG. They showed that the embryos were still able to reach 75% germination after 90 d of storage either at -1.6 or -2.4 MPa water potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was indeed the case in embryos stored in PEG at 5°C with ABA, at 5°C with ABA and HS and at 20°C without ABA or HS. However, a significant increase in MC was The longest effective storage period for Inga embryos was reported by Andréo et al (2006) working with nondried embryos stored in PEG. They showed that the embryos were still able to reach 75% germination after 90 d of storage either at -1.6 or -2.4 MPa water potentials.…”
Section: Discussionmentioning
confidence: 99%
“…affinis, seeds of which were used in this study, is a leguminous tree species typical of the riparian forests in south-eastern Brazil, and one of the most important species for ecological restoration of those ecosystems. Its seeds are recalcitrant and have one of the worst storabilities known (Bilia et al, 1999;Barbedo and Cicero, 2000;Faria et al, 2004;Andréo et al, 2006). In order to develop storage protocols for recalcitrant seeds a better knowledge of the events associated with storage is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Esse condicionamento mostrou potencial para ampliar a capacidade de armazenamento das sementes recalcitrantes, provavelmente reduzindo o metabolismo intenso e desordenado das sementes como resultado da regulação da mobilização da água na semente (Andréo et al, 2006). Esse condicionamento poderia ser utilizado, também, para diminuir a disponibilidade hídrica para os fungos, limitando o desenvolvimento dos mesmos antes de causar prejuízos às sementes.…”
Section: Introductionunclassified
“…Essas sementes geralmente apresentam atividade metabólica intensa, tanto durante sua formação, quanto após sua colheita (Barbedo & Marcos Filho 1998, Castro et al 2004. Assim, métodos para o armazenamento das sementes recalcitrantes devem obrigatoriamente considerar a redução do metabolismo (Andréo et al 2006).…”
Section: Introductionunclassified
“…Andréo et al (2006), por sua vez, controlando a mobilização de água entre a semente e o meio, obtiveram embriões com germinação superior a 80% após 90 dias de armazenamento, também a 10 °C, quando mantidos em substratos com soluções de PEG a -2,4 MPa. Bilia et al (1998), estudando os limites de tolerância à dessecação dessas sementes, conseguiram armazená-las, na mesma temperatura utilizada por aqueles autores, por até 60 dias quando o teor de água foi reduzido até 50%.…”
Section: Introductionunclassified